Modeling Catchment-Scale Nitrogen Losses Across a Land-Use Gradient in the Subtropics - Hajati, Mithra-Christin; White, Shane; Moosdorf, Nils; Santos, Isaac R. (Frontiers in Earth Science, 2020)
Changing land use in subtropical and tropical catchments to farmland can result in higher nitrogen (N) loss to aquatic ecosystems. Here, we developed a lumped water and N balance model to estimate regional N losses to creeks at catchment scale within understudied subtropical catchments in Australia. The conceptual water balance model CoCa-RFSGD was extended by the nitrogen mass balance in top and subsoil by adding nitrogen cycle transformation estimates depending on meteorological, soil, and land-use properties. The model estimates the impact of pristine and agricultural land use on catchment-wide water quality using only low-order creek samples as water quality measurements of nitrate and nitrite (NOx) with increased model performance with increased agricultural coverage. The model revealed that an agricultural proportion of 3% in the study site drove a 3.5-fold increase of N losses to creeks and a 6.7-fold increase of N losses to the atmosphere compared to catchments without agriculture. Agricultural land use lost 92 kg-N ha−1, 85% of which evaded to the atmosphere and 15% was discharged via surface waters. A change from forest to cleared land may increase the total denitrification potential of a catchment. Overall, our lumped model provides a simple but effective tool to upscale local aquatic water quality measurements to the catchment scale, allowing for assessment of changing land use on aquatic N loads in areas with limited data availability.